Coordination and extraction properties of 1, 2-bis(diphenylphosphoryl)-benzene toward f-block element nitrates: Structural, spectroscopic and DFT characterization of the complexes. (1st April 2021) - Matveeva, Anna G.; Artyushin, Oleg I.; Pasechnik, Margarita P.; Stash, Adam I.; Vologzhanina, Anna V.; Matveev, Sergey V.; Godovikov, Ivan A.; Aysin, Rinat R.; Moiseeva, Aleksandra A.; Turanov, Alexander N.; Karandashev, Vasilii K.; Brel, Valery K.
Graphical abstract: Five complexes of 1, 2-bis(diphenylpsphoryl)benzene with f -element nitrates were synthesized and studied by IR spectroscopy and X-ray diffraction. Solution structure of all complexes was studied by IR and multinuclear NMR spectroscopy. Two uranyl complexes were characterized by DFT calculations. Extraction efficiency of ligand toward U(VI), Th(IV) and Ln(III) was revealed. Highlights: Coordination properties of ligand L toward f -block element nitrates were examined. Ligand L exhibits constant O, O-chelation in solid and solution. Nitrate ions show variable denticity on complexation in solid and solution. Efficiency of extraction correlates with the solution structure of model complexes. Improved method for the synthesis of ligand L is suggested. Abstract: Reaction of 1, 2-bis(diphenylpsphoryl)benzene 1, 2-[Ph2 (O)P]2 C6 H4 (L ) with f -element nitrates resulted in 1:1 and 1:2 complexes. The isolated complexes, namely, [UO2 (L )(NO3 )2 ]·MeCN (1 ), [UO2 (L )2 (NO3 )](NO3 )·MeCN (2 ), [Th(L )2 (NO3 )3 ](NO3 )·MeCN·H2 O (3 ), [La(L )2 (NO3 )3 ]·0.5MeCN·1.5H2 O (4 ), and [Lu(L)2 (NO3 )2 ](NO3 )·2MeCN (5 ) have been characterized by elemental analysis and IR spectroscopy. The structures of complexes 1, 2, and 5 have been determined by single-crystal X-ray crystallography. Intraligand π-stacking and interligand CH… π interaction have been observed in the crystalline complexes. The π-stacking and CH… π interaction energy in two uranyl complexes 1 and 2 have been estimated from Bader's AIM theory calculations performed at the DFT level. Solution structure of all complexes has been investigated by IR and multinuclear ( 1 H, 13 C, and 31 P) NMR spectroscopy. The formation of 1:3 complexes with lanthanum nitrate (IR, 31 P NMR) has been examined. Preliminary extraction study of U(VI), Th(IV), and Ln(III) from 2 M HNO3 into 1, 2-dichloroethane have shown that ligand L recovers U(VI), Th(IV), and La(III) in the same extent as its tetraphosphoryl analog 1, 2, 4, 5-[Ph2 (O)P]4 C6 H2 (L' ) but it recovers Eu(III), and Lu(III) by several times better than L' . Furthermore, an improved modified method for the synthesis of ligand L has been suggested.